Analisis Komunikasi Krisis Situasional Trans Tv (Studi Kasus Program Kopi Viral Episode Saipul Jamil): Situational Crisis Communication Analysis on Trans Tv (Case Study of the Saipul Jamil Episode Kopi Viral Program - Amalia, Lia; Hermansah, Tantan; Naschihah (Jisab, 2023)
The presence of Saiful Jamil in the Trans Tv Viral Coffee program invited a lot of criticism from the public. Saiful's presence is considered a form of glorification of perpetrators of sexual violence against children, so it is inappropriate to appear in public spaces such as television. This is what causes the emergence of a communication crisis in the Trans Tv media organization so it requires fast and appropriate crisis response steps. Based on the picture above, this study aims to determine the steps of crisis evaluation and crisis response of the Trans Tv organization, in dealing with a communication crisis caused by the emergence of Saiful Jamil in the Viral Coffee program. So basically it can be seen that this research uses a qualitative approach, with the case study method. Data collection is done by way of interviews, documentation, and observation. The data processing method uses the Miles and Huberman technique, with three stages namely, reduction, presentation, and conclusion. Meanwhile, the theory used is Situational Communication Crisis Theory, which was introduced by Coombs. The results of this study indicate that the case crisis experienced by Trans TV, is categorized as an intentional crisis, and the crisis response steps used are diminished and rebuilt.